Review on Various Compatibilizers and its Effect on Mechanical Properties of Compatibilized Nylon Blends. Issue 6 (13th April 2017) - Aparna, S.; Purnima, D.; Adusumalli, Ramesh Babu
ABSTRACT: Nylon 6 blends such as polyamide 6/acrylonitrile–butadiene–styrene and polyamide 6/polypropylene are among the commercially successful blends, having varied applications ranging from automobile parts to construction industry. Nylon 6 blends can be made supertough based on other polymers involved. Nylon 6 blends are immiscible, and the use of compatibilizers can increase the interfacial adhesion between the polymers. Amount of compatibilizer plays a key role in defining the size distribution, dispersion, and adhesion between the polymers. In this paper, a detailed review on the compatibilizers used and the effect of compatibilizer on the mechanical and impact properties of the blends has been given. GRAPHICAL ABSTRACT: